Розвиток румунської етнології: історія та сучасність - Олтяну, А. (Народна творчість та етнологія, 2011)
This paper presents a short history of Romanian scholarship in the field of ethnology, with an emphasis on terminological questions (distinctions between folklore, ethnography, ethnology, anthropology that are made by Romanian scholars and specialists) and different scholarly institutions specializing in ethnology (universities, archives, institutes). It also documents the dawning of the rising interest in folk culture, designates the first collections of folklore, both scientific and private, as well as the main directions of Romanian scholarship in a diachronic perspective.